Clinically meaningful change for the chair stand test: monitoring mobility in integrated care for older people. Issue 5 (26th August 2022) - Gonzalez‐Bautista, Emmanuel; de Souto Barreto, Philipe; Salinas‐Rodriguez, Aaron; Manrique‐Espinoza, Betty; Rolland, Yves; Andrieu, Sandrine; Vellas, Bruno; ,
Abstract: Background: Clinically meaningful changes in the five‐repetition chair stand test are essential for monitoring mobility in integrated care for older people. Recommendations for the clinically meaningful change of the chair stand test are not well known. Our study aimed to estimate the absolute and relative clinically meaningful changes for older adults' five‐repetition chair stand test. Methods: We applied distribution‐based and anchor‐based methods in addition to receiver operator characteristics analyses to a population‐based study of community‐dwelling adults (SAGE Mexico study, n = 897) to derive the clinically meaningful change in the chair stand test. We used three self‐reported clinical anchors: moving around, vigorous activities, and walking 1 km. Our primary outcome was the incidence of disability for basic activities of daily living (ADL). Secondly, we examined our estimates of clinically meaningful change in a clinical trial population of healthy volunteers (MAPT, France, study n = 1575) concerning the risk of incident ADL disability. Results: The age of SAGE Mexico participants ranged from 60 to 96 years; mean (SD) = 69.0 (6.2); 54.4% were female. Their baseline chair stand time averaged 12.1 s (SD = 3 s). Forty‐eight participants (5.6%) showed incident disability over 3 years. The absolute and relative clinically meaningful change cut points found over 3 years of follow‐up were 2.6 s and 27.7%, respectively. Absolute clinically meaningful change ranged from 0.5 to 4.7 s, depending on the estimation method. Relative clinically meaningful change ranged from 9.6 to 46.2%. SAGE Mexico participants with absolute and relative clinically meaningful declines (increasing 2.6 s and 27.7% from baseline time, respectively) showed an increased risk of ADL disability [aRR = 1.93; P = 0.0381; 95% CI (1.05, 3.46) and aRR = 2.27; P = 0.0157; 95% CI (1.22, 4.10)], respectively, compared with those without a clinically meaningful decline. MAPT participants [age range = 70–94; mean (SD) = 75.3 (4.4); 64.8% female; incident ADL disability over 5 years = 145(14.8%)] with a relative clinically meaningful decline (≥27.7% from baseline over 3 years) had a 74% higher risk of incident ADL disability than their counterparts [aHR = 1.74; P = 0.016; CI95% (1.11, 2.72); mean follow‐up of 58 months]. Conclusions: Community‐dwelling older adults with an increase of 3 s or 28% in chair stand test performance over 3 years (approximately 1 s or 10% per year) could be the target of interventions to enhance mobility and prevent incident disability.